2014
DOI: 10.1056/nejmoa1401329
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery versus Intensive Medical Therapy for Diabetes — 3-Year Outcomes

Abstract: BACKGROUND In short-term randomized trials (duration, 1 to 2 years), bariatric surgery has been associated with improvement in type 2 diabetes mellitus. METHODS We assessed outcomes 3 years after the randomization of 150 obese patients with uncontrolled type 2 diabetes to receive either intensive medical therapy alone or intensive medical therapy plus Roux-en-Y gastric bypass or sleeve gastrectomy. The primary end point was a glycated hemoglobin level of 6.0% or less. RESULTS The mean (±SD) age of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
848
1
50

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,420 publications
(936 citation statements)
references
References 24 publications
37
848
1
50
Order By: Relevance
“…It achieves substantial and sustained weight loss, co-morbidity resolution, and improvements in quality of life and is associated with extended lifespan [3][4][5]. A systematic review has indicated that it is cost effective [6,7].…”
mentioning
confidence: 99%
“…It achieves substantial and sustained weight loss, co-morbidity resolution, and improvements in quality of life and is associated with extended lifespan [3][4][5]. A systematic review has indicated that it is cost effective [6,7].…”
mentioning
confidence: 99%
“…Schauer et al (28,29) in a single-center RCT included 150 patients with T2DM and BMI 27-43 kg/ m 2 into intensive medical therapy alone or intensive medical therapy plus either RyGB or sleeve gastrectomy (SG) group. The number of patients was equally distributed between the treatment arms.…”
Section: Surgery Versus Conventional Treatmentmentioning
confidence: 99%
“…Schauer and colleagues (28,29,42) explored an effect of RyGB and SG on the treatment of T2DM (primary outcome was HbA1c <6.0%, with or without diabetes medications) among patients with BMI 27-43 kg/m 2 , as part of their RCT comparing surgery versus best medical treatment. A total of 50 patients were included in each group.…”
Section: Sg Versus Gastric Bypassmentioning
confidence: 99%
“…22 Among patients with DM, bariatric surgery reduced glycated hemoglobin (HbA 1c ) level and number of DM medications at 3-year follow-up in the recent Surgical Treatment and Medications Potentially Eradicate Diabetes Efficiently (STAMPEDE) trial. 23 Other risk factors also improve with weight loss. Weight loss due to lifestyle change, 24 Orlistat, 22 or bariatric surgery 25 reduces systolic blood pressure (SBP).…”
Section: Potential Cardiovascular Benefits Of Weight Lossmentioning
confidence: 99%
“…Bariatric surgery increased highdensity lipoprotein cholesterol (HDL-C) levels, decreased triglyceride levels, and had no effect on low-density lipoprotein cholesterol (LDL-C) levels in the STAMPEDE trial. 23 In one nonrandomized study, women who lost weight after completing a calorie-restriction protocol were found to have decreased C-reactive protein. 26 This strong relationship between weight and prognosis has been called into question for high-risk patients by 2 observations.…”
Section: Potential Cardiovascular Benefits Of Weight Lossmentioning
confidence: 99%